PENERAPAN GOOD CORPORATE GOVERNANCE DENGAN METODE SELF ASSESSMENT (Studi Pada Kantor Pos Surabaya 60000) - Kumalasari, Erni (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out and to analyze company management at PT. Pos Indonesia (Persero) Surabaya area which is located on Jalan Kebon Rojo no. 10, by using self assessmentmethod. Based on the result of analysis and discussion related to the proper companymanagement which is performed by using self assessment method, it can be concluded that aproper company management at PT. Pos Indonesia (Persero) Surabaya Area 60000 has beenrealized in accordance with clean moral, transparency and professionalism (BTP) which areimplemented in each job description and in the regulations as well as in the policies which aredetermined by the head office. This independent result which is stated in the key performanceindicator (KPI) reflects a good individual performance. The relation among employees incarrying out their tasks is to give additional value to the company. This independent assessmentis, of course, cannot be separated from the important role of auditingÂ  and quality controldepartment who perform monitoring as well as to give suggestion recommendation for theimportance of company welfare. The validity of independent assessment also involves the roles ofthe employees from different working units and customers in the assessment. Keywords:Â  Good Corporate Governance, Clean, Transparency and Professionalism (BTP),Independent Assessment.